Irish women in medicine, c.1880s-1920s : Origins, education and careers - Kelly, Laura, 1986- (Book collections on Project MUSE., 2012)
This book is the first comprehensive history of Irish women in medicine in the late nineteenth and early twentieth centuries. It focuses on the debates surrounding women's admission to Irish medical schools, the geographical and social backgrounds of early women medical students, their educational experiences and subsequent careers. It is the first collective biography of the 760 women who studied medicine at Irish institutions in the period and, in contrast to previous histories, puts forward the idea that women medical students and doctors were treated fairly and often favourably by the Irish medical hierarchy. It highlights the distinctiveness of Irish medical education in contrast with that in Britain and is also unique in terms of the combination of rich sources it draws upon, such as official university records from Irish universities, medical journals, Irish newspapers, Irish student magazines, the memoirs of Irish women doctors, and oral history accounts.